2005
DOI: 10.1002/pbc.20621
|View full text |Cite
|
Sign up to set email alerts
|

Acute graft‐versus‐host disease of the heart

Abstract: Graft-versus-host disease (GVHD) is a frequent cause of morbidity and mortality after bone marrow transplantation. Acute GVHD most commonly involves the skin, gastrointestinal tract, and liver. Involvement of other organ systems is rare and remains controversial. We report a patient with GVHD who suffered a fatal ventricular arrhythmia shortly after bone marrow transplantation. Autopsy of the heart showed lymphocyte infiltration. Investigations for cardiotrophic viruses were negative, and chimerism analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Although rare, clinically significant GVHD involving the heart is often fatal, with a reported mortality rate of 43%. 2,3 Only 15 cases of GVHD with cardiac involvement have been published; the cardiac findings in these cases were bradyarrhythmia, coronary artery disease, cardiomyolysis and polyserositis-induced pericardial effusion. 4 Three cases of sudden cardiac death with autopsy-proven multi-vessel coronary disease have been reported.…”
mentioning
confidence: 99%
“…Although rare, clinically significant GVHD involving the heart is often fatal, with a reported mortality rate of 43%. 2,3 Only 15 cases of GVHD with cardiac involvement have been published; the cardiac findings in these cases were bradyarrhythmia, coronary artery disease, cardiomyolysis and polyserositis-induced pericardial effusion. 4 Three cases of sudden cardiac death with autopsy-proven multi-vessel coronary disease have been reported.…”
mentioning
confidence: 99%
“…DEGs in biopsies from subjects under SIS without rejection and with R as well as from D biopsies were compared using microarray-based gene expression assay on FFPE tissue RNA (Sensation Plus). This method was previously used exclusively in cancer-related studies [23][24][25] and showed a significant analytic performance correlation with classic gene expression microarray assays. Significant differences in gene expression profiles were observed among the three patient groups, with the FCRx biopsies showing a distinct profile.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known manifestations of GVHD include dermatologic, gastrointestinal, hepatic, pulmonary, musculoskeletal, and hematologic manifestations and sicca syndrome. [1][2][3] Cardiac manifestations have rarely been reported to be a target of GVHD and can present as bradycardia, coronary artery disease, sudden cardiac death, or cardiomyolysis. [1][2][3] Bradyarrhythmia has been reported to occur with acute GVHD or with an acute flare of chronic GVHD in the form of sinus node dysfunction or AV block.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Cardiac manifestations have rarely been reported to be a target of GVHD and can present as bradycardia, coronary artery disease, sudden cardiac death, or cardiomyolysis. [1][2][3] Bradyarrhythmia has been reported to occur with acute GVHD or with an acute flare of chronic GVHD in the form of sinus node dysfunction or AV block. 1,3,4 These findings appear to be secondary to immunologic reaction or cytokines released during GVHD.…”
Section: Discussionmentioning
confidence: 99%